Digital Transformations in Care for Older People Critical Perspectives - Hirvonen, Helena; Tammelin, Mia; Hänninen, Riitta; Wouters, Eveline J.M (Taylor & Francis, 2022)
The book investigates digitalisation in care for older people by giving insight into service users' and professionals' opportunities to digital agency in the context of European welfare states. With a focus on service users and providers experiences of digital care, the contributions address the manifold and often contradictory consequences of active ageing policies and innovation programmes. To assess digital agency of older people, ageism and co-creation in the innovation processes as well the use of digital platforms are addressed, while care professionals' digital agency is examined through empirical cases that focus on the interaction between human and non-human actors in long-term care services, the temporality and spatiality of care, and the organisational requirements for successful implementation of digital technologies. From a variety of conceptual and theoretical viewpoints, the chapters provide a comprehensive and timely overview of ways to address the phenomena of ageing and digitalisation. The book provides critical vantage points to academic readership, health and social care professionals, policymakers, other stakeholders as well as the general audience on the effects of digitalisation in care for older people.